TambaPlus Parentesco: assessment of the economic impacts and costs of the technological solution - Melo, Maria Clara da Cruz de; Muñoz, Andrea Elena Pizarro; Carvalho, Elizangela de Franca Carneiro; Sousa, Diego Neves de; Alves, Anderson Luis; Oliveira, Deise Maria; Mori, Silvia Satiko Onoyama; Iwashita, Marina Keiko Pieroni (Science & Technology Journals, 2025)
The study aimed to evaluate the multidimensional impacts of the “TambaPlus Parentesco” technology, an innovation designed for the tambaqui production chain. For this purpose, Embrapa’s reference methodology for assessing the impacts of the Technologies generated was applied. Traditionally, the production of native fish in the Amazon has been associated with artisanal fishing, and the modernization of the sector has always depended on the collaboration between different actors such as farmers’ associations, public authorities, and research institutions, with the purpose of guiding fish farmers on the importance of monitoring the kinship of broodstock raised in ponds. In 2023, Amazonian fish farming faced major challenges, such as the effects of drought, the need for specific local regulations, and competition with exotic species. Despite these difficulties, the increasing emphasis on sustainability has stimulated the consolidation of the market for native fish, especially in regions where tambaqui holds significant economic relevance. In this context, TambaPlus Parentesco emerges as a strategic tool to enhance fish quality through genetic parentage analysis, while simultaneously fostering sustainable practices in the aquaculture sector.